The undernourished curriculum: What happened to nutritional education in the medical curriculum? - Milosavljevic, Katarina; Meng, Jessica; Sahoo, Varsha; Trac, Kevin; Lopez, Jelissa Hernandez; Kaur, Saranjeet; Raghunathan, Anaha; Ali, Kamilah (Frontiers in Nutrition, 2025)
Nutrition is a cornerstone of disease prevention and health promotion, yet medical education, particularly within osteopathic schools, continues to fall short in preparing future physicians to address nutrition in clinical care. Despite the rising burden of diet-related conditions such as obesity, diabetes, and cardiovascular disease, most United States medical students receive fewer than the recommended 25 h of nutrition education. This perspective article explores the current state of nutrition education in osteopathic medical schools, examines the role of emerging clinical models such as “Food is Medicine,” and outlines opportunities for reform that align with the holistic philosophy of osteopathic medicine.